Влияние препарата полифенолов и диазепама на поведенческие реакции и саногенез при дозированных травмах десневого края годовалых крыс = The influence of the preparation of polyphenols and diazepam on behavioral reactions and sanogenesis at the dosed traumas of the gingival margin of one year’s rats - Nikolaeva, Anna Vladimirovna (Journal of Education, Health and Sport, 2016)
Nikolaeva A. V. Влияние препарата полифенолов и диазепама на поведенческие реакции и саногенез при дозированных травмах десневого края годовалых крыс = The influence of the preparation of polyphenols and diazepam on behavioral reactions and sanogenesis at the dosed traumas of the gingival margin of one year’s rats. Journal of Education, Health and Sport. 2016;6(2):18-23. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45508 http://ojs.ukw.edu.pl/index.php/johs/article/view/3374 https://pbn.nauka.gov.pl/works/711914 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. УДК: (616.311-003.9+615.214.22-035.2):599.323.4 UDC: (616.311-003.9+615.214.22-035.2):599.323.4 ВЛИЯНИЕ ПРЕПАРАТА ПОЛИФЕНОЛОВ И ДИАЗЕПАМА НА ПОВЕДЕНЧЕСКИЕ РЕАКЦИИ И САНОГЕНЕЗ ПРИ ДОЗИРОВАННЫХ ТРАВМАХ ДЕСНЕВОГО КРАЯ ГОДОВАЛЫХ КРЫС THE INFLUENCE OF THE PREPARATION OF POLYPHENOLS AND DIAZEPAM ON BEHAVIORAL REACTIONS AND SANOGENESIS AT THE DOSED TRAUMAS OF THE GINGIVAL MARGIN OF ONE YEAR’S RATS А. В. Николаева A. V. Nikolaeva Государственное учреждение «Институт стоматологии Национальной Академии Медицинских Наук Украины» SE «The Institute of Stomatology National Academy of Medical Sciences of Ukraine» Реферат В опытах на 22-х крысах 12-ти мес. возраста изучено влияние препарата полифенолов фитоседа и транквилизатора диазепама на процессы заживления стандартных травм десны. У активных по суммарной двигательной и поисковой активности крыс заживление наступало раньше, чем у пассивных животных. Введение препаратов природного происхождения – фитоседа и синтетического – диазепама нивелировало эти различия. Диазепам снижал сроки полного заживления, а фитосед стимулировал процессы саногенеза. Отмечается снижение исследовательской и поведенческой активности старых крыс от полноценности рациона их питания. Ключевые слова: растительные полифенолы, дозированная травма десны, заживление, фитосед, диазепам, крысы. A.V. Nikolaeva SE «The Institute of Stomatology National Academy of Medical Sciences of Ukraine» THE INFLUENCE OF THE PREPARATION OF POLYPHENOLS AND DIAZEPAM ON BEHAVIORAL REACTIONS AND SANOGENESIS AT THE DOSED TRAUMAS OF THE GINGIVAL MARGIN OF ONE YEAR’S RATS Summary At the experiments on the 22 rats, 12 months age was studied the influence of the preparation of Phytosedum polyphenols and the tranquilizer of Diazepamum on the healing process of the standart injuries of gums. The assessment of behavioral responses was carried out for 5 minutes in rats in the test "open field" - were registered parameters, that describing their motor activity. The Aim of this research was to study the influence of the preparation of polyphenols on the healing process of the standard injuries of the mucous membrane gingiva depending on the type of conduct and the usefulness of the diet of old rats. Materials and methods. In the experiment were used 22 albino rats of 12 months of age. Before starting the experiment was evaluated the behavioral responses of all animals in the test "open field." Then rats were randomly divided into 4 groups, which daily orally administered: 1st group (5 rats) - water (1.0 ml / kg); 2d group (5 rats) - water - 1.0 ml / kg; 3rd group (6 rats) "BDP + diazepam"; 4th group (6 rats) - ("BDP + phytosedum " - 1.0 ml / kg in 1: 1 dilution). Results and conclusions. Established the dependence the rate of the occurrence of complete healing of injuries from "psycho" rats. In terms of total active motor and search activity of rats healing occurs earlier than in passive animals. The introduction of drugs of natural origin - fitoseda and synthetic - of Diazepamum offsetting these differences. Diazepam lowerd terms of the full adhesion, and Phytosedum - stimulate of the process of sanogenesis fitosed. Despair reduction of research and the behavioral activity of old rats from the usefulness of their diet. Key words: plant polyphenols, dosed trauma of gums, healing, fitosed, diazepam, rats.